Peningkatan Keaktifan Belajar Siswa Melalui Media Video Pembelajaran Audio-Visual Pada Pembelajaran IPA Kelas V Sekolah Dasar - Ni Kadek Sutami Yanti; I Made Ari Winangun; I Made Adi Nugraha Tristaningrat (Jayapangus Press, 2026)
This study aimed to improve students’ learning activeness through the use of audio-visual instructional video media in fifth-grade science learning at SD Saraswati Tabanan. The study employed Classroom Action Research conducted in two cycles, each involving planning, action implementation, observation, and reflection. The research subjects were 28 fifth-grade students, consisting of 15 male and 13 female students. Data were collected through observation, documentation, and field notes. The main instrument was a student learning activeness observation sheet covering five indicators: paying attention to the teacher’s explanation and video presentation, asking questions, answering questions, participating in discussions, and expressing opinions. The data were analyzed using descriptive quantitative analysis by calculating the percentage of students’ learning activeness in each cycle. The findings revealed that audio-visual instructional video media improved students’ learning activeness in science learning. The average percentage of students’ activeness increased from 61.6% in Cycle I to 80.4% in Cycle II. Improvement occurred across all indicators, particularly in asking questions and expressing opinions. The novelty of this study lies in the use of audio-visual instructional video media not only as a tool for delivering science content, but also as a stimulus for strengthening students’ participation, confidence, and learning interaction. These findings imply that audio-visual instructional videos, when combined with questioning and group discussion strategies, can support more active, interactive, and meaningful science learning in elementary schools.